Link and Match Program to Establish Competence of Fiber Optical Technology: A Case Study at VHS Sore Tulungagung with Telkom Indonesia - Muhammad Ja’far Shodiq; Yoto Yoto; Nunung Nurjanah (Belantika Pendidikan, 2022)
This study aims to identify and describe the link and match program carried out by schools and industry, especially in the field of fiber optic technology. The research approach used is descriptive qualitative. The technique used in collecting data is through interviews, observation and documentation. The result of this research is a link and match program The activities carried out by SMK SORE Tulungagung with Telkom Indonesia in the field of fiber optic technology are carried out in the form of aligning the curriculum in the industrial class in the field of fiber optic technology, teacher human resource training activities in the field of fiber optic technology, procurement of facilities and infrastructure to support fiber optic installation practices in schools, and implementation of learning activities in schools and in industry.